2007
DOI: 10.3892/or.17.4.713
|View full text |Cite
|
Sign up to set email alerts
|

Increased BRCA1 protein in mammary tumours of rats fed marine ω-3 fatty acids

Abstract: Any factor affecting BRCA gene regulation may be of interest in the prevention of breast tumourigenesis. We studied the influence of dietary docosahexaenoic acid (DHA), a major ˆ-3 fatty acid present in marine products, on rat autochthonous mammary tumourigenesis. DHAsupplementation significantly reduced the incidence of tumours (30%, P=0.007) and led to a 60% increase (P=0.02) in BRCA1 protein level. Since DHA influences the product of a major tumour suppressor gene, this finding may contribute to the observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
0
26
0
2
Order By: Relevance
“…These include dietary supplementation of mouse transplantable tumors (71) and human cell xenograft models (72,73) as well as chemically induced tumors in rats (74,75,76). A recent report showed that dietary DHA-induced reduction in mammary tumors in a rat model was accompanied by a 60% increase in BRCA1 tumor suppressor protein (77). Interestingly, n-3 fatty acid-enriched diets enhanced the efficiency of doxorubicin (78) and mitomycin C (79) in inhibiting tumor growth and strengthened the inhibitory effect of tamoxifen in estrogendependent xenografts (80).…”
Section: Models Of Breast Cancermentioning
confidence: 99%
“…These include dietary supplementation of mouse transplantable tumors (71) and human cell xenograft models (72,73) as well as chemically induced tumors in rats (74,75,76). A recent report showed that dietary DHA-induced reduction in mammary tumors in a rat model was accompanied by a 60% increase in BRCA1 tumor suppressor protein (77). Interestingly, n-3 fatty acid-enriched diets enhanced the efficiency of doxorubicin (78) and mitomycin C (79) in inhibiting tumor growth and strengthened the inhibitory effect of tamoxifen in estrogendependent xenografts (80).…”
Section: Models Of Breast Cancermentioning
confidence: 99%
“…A review of 81 rodent studies concluded that dietary omega-6 fatty acids dose-dependently accelerate mammary tumorigenesis (11). Conversely, dietary EPA and DHA prevent mammary tumor development in animals (12)(13)(14)(15). The effect of omega-3 and omega-6 intake on breast cancer risk in humans has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…(54) Interestingly, n-3 fatty acidenriched diets enhanced the efficiency of doxorubicin (55) and mitomycin C (56) in inhibiting tumor growth and strengthened the inhibitory effect of tamoxifen in estrogen dependent xenografts.These studies point to a potential value of n-3 fatty acids as adjuvant to standard chemotherapy. (58) There are many molecular mechanisms by which omega-3 PUFA may exerts their potential effects on the cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-γ negatively regulates several genes, including NF-κB gene. The ability of PPAR-γ to inhibit NF-κ B expression is important in breast cancer progression (5,6).…”
Section: Introductionmentioning
confidence: 99%